MORE DISCUSSION ABOUT THE TIME OF APPEARANCE OF VIET BELIEFS IN THE MOTHER GODDESSES OF THREE REALMS - Cao Thế Trình (Tạp chí Khoa học Đại học Đà Lạt)
On the basis of the analysis of myths, old royal decrees (sắc phong) and historical texts, the author argues that the worship of the Mother Goddesses could have appeared as early as associated beliefs in fertility by agricultural residents. It is thought that the belief in the Mother Goddesses of Three Realms is a custom linked to the worship of the God of Wealth by the small business class, associated with the need for an assistant goddess to give fortune to those who work as business people. Therefore, the belief in the Mother Goddesses of Three Realms could not have appeared earlier than the beginning of the seventeenth century because the documentation of Vietnamese authors and Western clergy at that time did not mention the myth and worship of the Lieu Hanh Mother in the Kingdom of Tonqueen (Đàng ngoài). This kind of worship was considered a belief system formed and developed on the basis of small business activities. When the country’s economy operated under market mechanisms, this belief system expanded strongly in both temples and shaman rituals (lên đồng), which are considered a waste of the time, money and health of believers. In order for the belief in the Mother Goddesses of Three Realms to develop in a healthy manner in accordance with its good nature, according to the author, it is necessary to be very cautious about the “commercialization” of this belief system in general and shaman rituals (lên đồng) in particular.